Implementation Of The Iot Device For Sit-Up Counting Based On ESP 8266 - Rifai, Jefri Andri; Styawati, Styawati; Wijaya, Rio (LPPM STIKI Malang, 2024)
Sit ups are a type of strength exercise that functions to strengthen muscles. Sit up movements are usually calculated manually, but as technology develops, it is necessary to innovate to build a digital technology-based sit up movement counting tool. The goal is to provide a sit up instrument that is able to accurately calculate the number of sit ups that have been done. The tool is made based on digital technology using the internet of things (IoT). In making this tool, the author uses 2 LDR sensor modules and 2 KY008 laser sensors installed to detect the shoulder. If one of the light sensors in the form of an LDR module is not disconnected from the light displayed by the laser sensor, then the series of sit up counting tools with this application will not calculate the sit up acquisition. The sit up counter tool will calculate if the sit up position is perfect and cut off the laser light, it will send the results of the sit up to the MySQL database which will later be displayed in the web server. This tool is easy to use and portable or easy to move. The way this tool works is quite easy, the user only needs to choose the type of exercise needed, then the tool will calculate the movements done and the user just needs to lie on the side of the tool and prepare to do the display according to the activity to be done. Then the tool will calculate automatically and will enter the website data.